PERGESERAN PERAN DAN FUNGSI RADIO SUARA SURABAYA DARI RADIO INFORMASI MENJADI RADIO PENGADUAN - Sampoerno Sampoerno; Seto Herwandito; Dewi Kartika Sari (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2018)
This study aims to identify factors causing the shift function of Radio Suara Surabaya. This research also explains the reason for the shift to occur. In examining the shift of Radio Suara Surabaya function from its original function and why the shift occurred, the researcher uses a qualitative research approach with descriptive research type. In the early stages of this study, the researchers identified the initial function of the establishment of Radio Suara Surabaya as an information radio. Furthermore, it describes the shift of voice function of Radio Suara Surabaya into a grievance function. Finally the researchers identified the reason for the radio function shift. At the stage to maintain the credibility of research data, researchers conducted data triangulation by conducting literature studies on radio and radio management.